Putative Astroglial Dysfunction in Schizophrenia: A Meta-Analysis of 1H-MRS Studies of Medial Prefrontal Myo-Inositol - Das, Tushar Kanti; Dey, Avyarthana; Sabesan, Priyadharshini; Javadzadeh, Alborz; Théberge, Jean; Radua, Joaquim; Palaniyappan, Lena (Frontiers in Psychiatry, 2018)
Background Several lines of evidence support a role for astroglial pathology in schizophrenia. Myo-inositol is particularly abundant in astroglia. Many small sized studies have reported on myo-inositol concentration in schizophrenia, but to date these have not been pooled to estimate a collective effect size. Methods We reviewed all proton magnetic resonance spectroscopy (1H-MRS) studies reporting myo-inositol values for patients satisfying DSM or ICD based criteria for schizophrenia in comparison to a healthy controls group in the medial prefrontal cortex published until February 2018. A random-effects model was used to calculate the pooled effect size using metafor package. A meta-regression analysis of moderator variables was also undertaken. Results The literature search identified 19 studies published with a total sample size of 585 controls, 561 patients with schizophrenia. Patients with schizophrenia had significantly reduced medial prefrontal myo-inositol compared to controls (RFX standardised mean difference=0.19, 95% CI [0.05-0.32], z=2.72, p=0.0067; heterogeneity p = 0.09). Studies with more female patients reported more notable schizophrenia-related reduction in myo-inositol (z=2.53, p=0.011). Discussion We report a small, but significant reduction in myo-inositol concentration in the medial prefrontal cortex in schizophrenia. The size of the reported effect indicates that the biological pathways affecting the astroglia are likely to operate only in a subset of patients with schizophrenia. MRS myo-inositol could be a useful tool to stratify and investigate such patients.